Efektivitas Model Pembelajaran Berbasis Permainan Edukatif dalam Meningkatkan Kecerdasan Jamak Anak Raudhatul Athfal - As’ad, Mahrus; Agustin, Mubiar; Rahman, Taufiq; Robayanti, Dinda (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
This study stems from the need for a learning model that can optimize the development of multiple intelligences in early childhood. The study aims to determine the effectiveness of a learning model that incorporates educational games in enhancing the abilities of children in Raudhatul Athfal (RA). The research method used is a quasi-experimental design, with data collection techniques including pretests, posttests, and observations, followed by data analysis using a T-test. The research subjects consisted of 40 children from one RA in Bandung Regency and another in Bandung City. This study not only measures the impact of educational games on multiple intelligences but also evaluates the development of the intelligences children already possess. The findings indicate that the learning model incorporating educational games is effective (p<0.05) in developing various aspects of children's intelligence. In addition to improvements in physical and linguistic intelligence, children also demonstrated significant progress in social skills, such as cooperation and empathy, as well as in intrapersonal abilities, including self-awareness and emotional regulation. Educational games also encourage active child engagement in the learning process, strengthening their intrinsic motivation to learn. These findings suggest that integrating educational games into the RA curriculum can serve as a holistic learning strategy, not only enhancing academic abilities but also fostering children's overall character development.